Is Group B Streptococcus Colonization Associated with Maternal Peripartum Infection in an Era of Routine Prophylaxis? - Venkatesh, Kartik K.; Vladutiu, Catherine J.; Glover, Angelica V.; Strauss, Robert A.; Stringer, Jeffrey S.A.; Stamilio, David M.; Hughes, Brenna; Dotters-Katz, Sarah (American Journal of Perinatology, 2020)
Objective This study aimed to assess whether colonization with group B streptococcus (GBS) is associated with maternal peripartum infection in an era of routine prophylaxis.Study Design This study presented a secondary analysis of women delivering ≥37 weeks who underwent a trial of labor from the U.S. Consortium on Safe Labor (CSL) study. The exposure was maternal GBS colonization and the outcome was a diagnosis of chorioamnionitis, and secondarily, analyses were restricted to deliveries not admitted in labor and measures of postpartum infection (postpartum fever, endometritis, and surgical site infection). Logistic regression with generalized estimating equations was used accounting for within-woman correlations. Models adjusted for maternal age, parity, race, prepregnancy body mass index, pregestational diabetes, insurance status, study site/region, year of delivery, number of vaginal exams from admission to delivery, and time (in hours) from admission to delivery.Results Among 170,804 assessed women, 33,877 (19.8%) were colonized with GBS and 5,172 (3.0%) were diagnosed with chorioamnionitis. While the frequency of GBS colonization did not vary by chorioamnionitis status (3.0% in both groups), in multivariable analyses, GBS colonization was associated with slightly lower odds of chorioamnionitis (adjusted odds ratio [AOR]: 0.89; 95% confidence interval [CI]: 0.83–0.96). In secondary analyses, this association held regardless of spontaneous labor on admission; and the odds of postpartum infectious outcomes were not higher with GBS colonization.Conclusion In contrast to historical data, GBS colonization was associated with lower odds of chorioamnionitis in an era of routine GBS screening and prophylaxis.Key Points
Keywords: pregnancy; GBS colonization; chorioamnionitis; peripartum infection